A= 7^4+2.7^3+3^3 phần 692
a,123-5(x+4)=38
b,(3.x-2^4).7^3=2.7^4
a) 123-5x-5.4=38
123-5x-20=38
103-5x=38
5x=103-38
x=(103-38):5=13
b)
(3.x-16).7^3=2.7^4
3x-16=2.7^4/7^3=2.7=14
3x=14+16=30
x=30/3=10
Tìm a
(3.a-24) . 73 = 2.74
(3a - 2^4 ).7^3 = 2.7.7^3
=> 3a - 16 = 2.7
=> 3a - 16 = 14
=> 3a = 30
=> a = 10
(3.x - 2 mũ 4) : 7 mũ 3 = 2.7 mũ 4
\((3.x-2^{4} ):7^3 =2.7^{4}\)
\(=>(3.x-16):7^{3} =2.7^{4}\)
\(=>3.x-16=2.7^{4}:7^{3}\)
\(=>3.x-16=2.7^{4-3}\)
\(=>3.x-16=2.7\)
\(=>3.x-16=14\)
\(=>3.x=14+16\)
\(=>3.x=30\)
\(=>x=30:3\)
\(=>x=10\)
\(\left(3x-2^4\right):7^3=\left(2.7\right)^4\)
\(\Rightarrow\left(3x-2^4\right)=2^4.7^4.7^3\)
\(\Rightarrow3x-2^4=2^4.7^7\)
\(\Rightarrow3x=2^4.7^7+2^4\)
\(\Rightarrow3x=2^4.\left(7^7+1\right)=16\left(7^7+1\right)\)
\(\Rightarrow x=\dfrac{16\left(7^7+1\right)}{3}\)
Sửa lại.
\((3x-2^{4}):7^{3}=2.7^{4}\)
\(=>3x-2^{4} =2.7^{4}.7^{3}\)
\(=>3x-2^{4} =2.7^{7}\)
\(=>3x=2.7^{7}+2^{4}\)
\(=>x=\dfrac{2.7^{7}+16}{3}\)
692 - 4. ( X . X3+ 17 ) = 27
=> 692 - 4 (x4 + 17) = 128
=> 4(x4 + 17) = 564
=> x4 + 17 = 141
=> x4 = 124
tới đây là bí rồi
(3x - 2^4) - 7^3 = 2.7^4
\(\Leftrightarrow3x-16=2.7^4+7^3=5145\Leftrightarrow3x=5161\Leftrightarrow x=\dfrac{5161}{3}\)
\(\left(3x-2^4\right)-7^3=2.7^4\\ \Leftrightarrow\left(3x-16\right)=2.7^4+7^3\\ \Leftrightarrow3x-16=5145\\ \Leftrightarrow3x=5145+16=5161\\ \Leftrightarrow x=\dfrac{5161}{3}\)
tìm x;
(3.x- 2^4).7^3=2.7^4
(3.x - 2^4) . 7^3 = 2. 7^4
(3.x - 16) . 343 = 2 . 2401
(3.x - 16) . 343 = 4802
3.x - 16 = 4802 : 343
3.x - 16 = 14
3.x = 14 + 16
3.x = 30
x = 30 : 3
x = 10
Tính gọn biểu thức :
a,-5.7^5+7^4:7^6.10-2.7^5
b,10^3+5.10^2+5^3:-13
(3x-2^4).7^3=2.7^4
=> 3x-2^4 = 2.7
=> 3x - 16 = 14
=> 3x = 30
=> x = 10
( 3x - 24 ) . 73 = 2.74
=> ( 3x - 16 ) = 2 .( 74 : 73 )
=> ( 3x - 16 ) = 2 . 7
=> 3x - 16 = 14
=> 3x = 30
=> x = 10
(3x-2^4).7^3=2.7^4
\(\left(3x-2^4\right).7^3=2.7^4\\ \Leftrightarrow3x-16=2.7^4:7^3\\ \Leftrightarrow3x=14+16\\ \Leftrightarrow3x=30\\ \Leftrightarrow x=10\)
Vậy...
\(\left(2x-2^4\right).7^3=2.7^4\)
\(\Leftrightarrow\left(2x-2^4\right)=2.7^4:7^3\)
\(\Leftrightarrow2x-2^4=2.7\)
\(\Leftrightarrow2x-16=14\)
\(\Leftrightarrow2x=30\)
\(\Leftrightarrow x=15\)
Vậy ..
( 3x - 24 ) . 73 = 2 . 74
( 3x - 16 ) . 343 = 4802
3x - 16 = 4802 : 343
3x - 16 = 14
3x = 14 + 16
3x = 30
x = 30 : 3
x = 10